Analysis of the role of metacognition based on process complex problem solving against mathematical understanding of statistics in the era pandemic COVID-19. (October 2020) - Rusmini, R; Harahap, F S W; Guntoro, F R
Abstract: This research aims to analyze the role of process complex problem solving based metacognition against mathematical understanding in the era pandemic Covid-19 at the Universitas Potensi Utama Medan. This research uses qualitative descriptive methods. The population of the study is information system students in the second semester of Universitas Potensi Utama Medan. The research subjects were Information Systems students in the 2 nd semester of SI C morning and SI B morning classes. To obtain research data, an instrument was used in the form of 2 contextual problems with metacognition questions in problem-solving and student questionnaire response sheets with 30 queries. Conclusions of the results of the study: 1) The role of metacognition increases with motivation in learning, namely process complex problem solving, 2) the level of mathematical understanding of students in solving mathematical problems of statistics increases significantly, 3) students' responses in learning mathematics show positive reactions, 4) Students in tryout I mostly experienced many obstacles but in tryout II students were already accustomed and learning outcomes improved significantly, 5) Student answer sheets are more varied and better. With online learning, students are trained in their metacognition roles independently.